Fundamentals of enzyme kinetics - Cornish-Bowden, Athel (Portland, 1995)
Since the first edition of the book was published in 1979, the development of techniques for studying and manipulating genes has transformed biochemistry. Nonetheless, enzymes remain at the heart of all living systems, and an understanding of how they operate is vital for understanding the chemistry of life. This book describes the principles of enzyme kinetics, with an emphasis on principles rather than an encyclopaedic accumulation of facts, to allow readers to fill in gaps themselves and proceed in the subject as far as they need to go. In this way it provides the basis for understanding enzyme kinetics, whether at the level of the undergraduate, the research student or the researcher.